Slavic *mokrъ, Irish ainmech ’wet, rain’ - P. Hamp, Eric (Slavia Centralis, 2020)
The author demonstrates the etymological connections among Baltic, Slavic, Albanian, and Celtic for the term ’wet’, reflected in PIE *mek- ( *mok-).